Pendampingan Manajemen Usaha pada UMKM Laundry dalam Upaya Meningkatkan Daya Saing - Ria Dwi Rahmawati; Pratama, Adita Aji Pratama; Tri Wahid; Arie Sofyan; Fanniya Dyah Prameswari; Mona Tiorina Manurung; Galih Panjalu Pramono; Dyah Purwaningrum; Ragil Saskya Yuniar Herawati (JURPIKAT, 2026)
Laundry Micro, Small, and Medium Enterprises (MSMEs) are one of the service sectors that are growing rapidly along with the increasing public demand for practical and efficient services. However, most laundry MSMEs still face problems in managing their business and marketing strategies that are still conventional. This Community Service (PKM) activity aims to provide business management assistance to one of the laundries MSME businesses in Mijen, Semarang to increase business competitiveness. The PKM implementation method includes initial observation, problem identification, training and assistance in business management and marketing. The results of the activity show an increase in understanding of the laundry MSME operators regarding the importance of structured business management and effective marketing strategies, which has an impact on increasing business visibility and the potential for increasing the number of customers.